Gene expression profiling of human umbilical vein endothelial cells overexpressing CELF2 as diagnostic targets in diabetes-induced erectile dysfunction - Daniyaer Nuerdebieke; Lizhong Yao; Lange Guo; Jiuzhi Li; Hongliang Jia; Yukui Nan (Frontiers in Molecular Biosciences, 2025)
BackgroundErectile dysfunction (ED) is a common complication of diabetes mellitus (DM), and because of its complex neurovascular etiology, the associated molecular pathogenic mechanisms are not fully understood. This study investigated the important functions and potential molecular regulatory roles of CELF2 in DMED.MethodsAn in vitro HUVEC model with CELF2 overexpression was successfully established via transfection with a CELF2-overexpressing lentiviral vector. The effects of CELF2 overexpression on cell proliferation and angiogenesis were assessed via CCK-8 and angiogenesis assays. RNA sequencing was employed to evaluate the gene expression profiles and alternative splicing events regulated by CELF2. An RNA-sequencing assay was performed to evaluate gene expression profiles and alternative splicing genes in HUVECs overexpressing CELF2, and an integration analysis was combined with GSE146078 data to detect potential target genes related to DMED.ResultsThe expression of genes related to angiogenesis and the immune response significantly increased with CELF2 overexpression, and the four hub genes associated with alternative splicing in aging and angiogenesis were CXCL2, CXCL10, IL-1A and IL-6.ConclusionCELF2 appears to be a key factor in DMED, influencing gene expression and alternative splicing related to angiogenesis and immune responses. The identified hub genes (CXCL2, CXCL10, IL-1A, and IL-6) are closely related to DMED and warrant further investigation to understand the underlying mechanisms and potential therapeutic implications.